2021
DOI: 10.1021/acsaem.1c01090
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Network Modified Mesoporous SnO2 for Enhanced Fill Factor in Perovskite Solar Cells

Abstract: The rise of perovskite solar cell performance lies in the increase of fill factor and open-circuit voltage, which depend on high film quality (shunt resistance) and efficient charge transportation (series resistance). Polymer passivation could suppress the film defects, while its poor conductivity leads to a trade-off between passivation quality and series resistance. Here we introduce a polymer network modified mesoporous SnO2 layer to reconcile this contradiction, in which the mesoporous SnO2 was partially c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Due to the electrical insulation of polymers, simultaneous improvement of stability and optoelectronic performance calls for an urgent demand for functional polymers. [ 95,236–240 ] In addition, the crystal quality of perovskites is sensitive to the amount and species of polymers by blending of perovskite precursors and polymers, and the distribution of polymers by the blending method is mainly enhanced at the surface and partial grain boundaries, which does not form an encapsulated perovskite film. In this regard, we conceive the following strategies to optimize the perovskite–polymer composite for the target of high‐performance multifunctional perovskite optoelectronics: (i)The high‐throughput platform equipped with machine learning and density functional theory, molecular dynamics simulation, or first‐principles theory should be applied to investigate the precise interaction between perovskites and polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the electrical insulation of polymers, simultaneous improvement of stability and optoelectronic performance calls for an urgent demand for functional polymers. [ 95,236–240 ] In addition, the crystal quality of perovskites is sensitive to the amount and species of polymers by blending of perovskite precursors and polymers, and the distribution of polymers by the blending method is mainly enhanced at the surface and partial grain boundaries, which does not form an encapsulated perovskite film. In this regard, we conceive the following strategies to optimize the perovskite–polymer composite for the target of high‐performance multifunctional perovskite optoelectronics: (i)The high‐throughput platform equipped with machine learning and density functional theory, molecular dynamics simulation, or first‐principles theory should be applied to investigate the precise interaction between perovskites and polymers.…”
Section: Discussionmentioning
confidence: 99%
“…3 On the other hand, combination of perovskites with silicon resulted in a monolithic tandem silicon/perovskite cell with a 1.68 eV bandgap perovskite which retained 95% of its initial PCE of 29% after 300 h of operation as reported by Al-Ashouri et al 4 Notably, the highest PCE values have been demonstrated upon employing a mesoporous PSC architecture (mp-PSC), 5 in which typically highly transparent mp metal oxides combining a high porosity and large surface area are used as electron transporting materials/layers (ETMs/ETLs) (e.g. titanium dioxide (TiO 2 ), 6 tin oxide (SnO 2 ) 7 ) or, alternatively as hole transporting materials/layers (HTMs/HTLs) (e.g. nickel oxide (NiO x ) 8 ).…”
Section: Introductionmentioning
confidence: 87%
“…Notably, the highest PCE values have been demonstrated upon employing a mesoporous PSC architecture (mp-PSC), 5 in which typically highly transparent mp metal oxides combining a high porosity and large surface area are used as electron transporting materials/layers (ETMs/ETLs) ( e.g. titanium dioxide (TiO 2 ), 6 tin oxide (SnO 2 ) 7 ) or, alternatively as hole transporting materials/layers (HTMs/HTLs) ( e.g. nickel oxide (NiO x ) 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The defects present on the SnO 2 ETL surface, such as Sn dangling bonds, cause charge traps and recombination, resulting in hysteresis, low efficiency, and device instability in the PSCs. Many approaches using fullerene derivatives, 94,95 small organic molecules, [96][97][98][99][100] polymers, [101][102][103] and inorganic compounds 104,105 have been implemented to passivate the surface defects of SnO 2 ETL. The dual passivation method is another approach to passivate the SnO 2 ETL surface more efficiently.…”
Section: Tin Oxidementioning
confidence: 99%